Cardiometabolic Corner: Updates from the International Chair on Cardiometabolic Risk - Jacobson, Anne (MD Conference Express, 2009)
There has been a significant increase in the consumption of refined sugars across the globe over the past 20 years, with the main source of this increase from sugar-sweetened beverages, including soft drinks, fruit drinks, energy drinks, and vitamin and other functional beverage waters. This article presents new updates on the relationship between sugar-sweetened beverages and the metabolic syndrome.